Vacuum level for opening the streak canal and measurement of machine-induced changes in teat tissue during milking of dairy camels (Camelus dromedarius) - Atigui, Moufida; Brahmi, Marwa; Sadan, Madeh; Alshanbari, Fahad A.; Dahmani, Khouloud; Salem, Wiem Ben; Hammadi, Mohamed; Marnet, Pierre-Guy (Frontiers in Veterinary Science, 2025)
This research aims to study some of the teat characteristics involved in milkability of dairy camels, including the relationship between teat anatomy and the vacuum needed to open the teat sphincter (VLOTS). It also investigates short-term machine milking-induced changes in teat tissue thickness and teat anatomical characteristics, as well as their implications for udder health in dairy camels. To study VLOTS, 10 dairy camels in mid-lactation (weight: 516.6 ± 19 kg; age: 13.4 ± 3.8 years; parity: 5 ± 1.8; average milk yield: 7.3 ± 0.8 L/day) were used in Experiment 1. VLOTS was measured 4 h after morning milking for all four teats using an apparatus called a vacuumeter, without a liner or pulsation. Measurements were repeated three times at 2-day intervals and considered as repetition. Teat canal length (TCL), teat wall thickness (TWT), teat cistern separation wall thickness (TSWT), teat cistern diameter (TCD), and teat length were measured using ultrasound. Experiment 2 was performed on six dairy camels in late lactation (weight: 460 ± 55.15 kg; age: 10.2 ± 2.4 years; parity: 3.5 ± 1.0; average milk yield: 3.6 ± 0.7 L/day). External teat measurements (length, barrel, and apex diameters) were recorded with a caliper. Pre-and post-milking teat-end thickness (TET) were evaluated with a cutimeter at 2 cm from the teat end. Ultrasound imaging was performed pre-and post-milking to determine TCL, TWT, TCD, and teat apex diameter (TAD). Milk ejection time and total milking duration were recorded. Residual milk volume was estimated after an injection of 10 IU oxytocin. Milk samples were taken for somatic cell count (SCC). The results showed that only 50 teats out of 120 observations exhibited milk flow at a vacuum up to 70 kPa. Teats were divided into three groups: Group 1 included easy-opening teats that opened at a vacuum level of less than 30 kPa; group 2 included teats that were hard to open, requiring a higher vacuum (31 up to 69 kPa); and group 3 included teats that did not show milk flow at a vacuum higher than 70 kPa. The mean VLOTS for groups 1 and 2 were 19.39 ± 0.66 kPa and 47.13 ± 2.14 kPa, respectively. VLOTS was positively and highly correlated with TCL, TWT, and TSWT (r = 0.71, r = 0.62, and r = 0.51, respectively, p < 0.001) and negatively correlated with teat length and diameter (r = −0.50 and r = −0.30, respectively, p < 0.01). Observation of teats immediately after cluster removal revealed a 15.4% decrease in TET. TCL and TWT increased by 20.3 and 40.5%, respectively, while TCD and TAD decreased by 40.3 and 19.9%, respectively, after milking. This suggests the stretching of the teat extremity and congestion of the teat barrel wall. The mean SCC recorded in this study was 149.6 103 cells/mL, varying from 37.5 103 cells/mL to 287.5 103 cells/mL. This study confirms the need for a high vacuum level to overcome the sphincter barrier in dromedary camels. However, it suggests the deleterious effect of large camel teats in a cow’s liner.